Perancangan Mesin Penghitung Benih Kentang G-Nol di PT. Kentang Holando Sejahtera - Faaidah, Husnul; Jopa, Willis Islamiati; Madril, Fanie Novianti; Saefuloh, Saefuloh; Srimurni, Rafika Ratik; Susanti, Susanti (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to design a simple and affordable G-0 potato seed counting machine to improve accuracy and efficiency at PT. Kentang Holando Sejahtera. A descriptive qualitative approach was used, involving field observation, design modeling with SketchUp, and manual Cost Budget Planning (RAB) as the cost analysis method. The machine is designed with dimensions of 40×35×40 cm and a 40×40×20 cm hopper, with a capacity of approximately 3,000 seeds. Main materials include steel plate, round steel, and angle iron. Key components consist of a manual crank handle, magnetic sensor, and digital counter. The results show that the machine can be built at a cost of around Rp900,000 and increases work efficiency by 30–40%. It is suitable for small- to medium-scale agribusinesses, user-friendly, and replicable in low-tech agricultural settings. Further prototype testing and development into a semi-automatic system are recommended.